Inflation, Complexity and Endogenous Growth - Sequeira, Tiago Neves (2019)
In this article, we argue that inflation increases complexity pertaining to knowledge production (or R&D). Then, we expand a recently developed complexity index based on entropy to include the effect of inflation. As a result of this new mechanism in an endogenous growth model, inflation is no longer superneutral. In the model, inflation can decrease economic growth in a nonlinear way, a sudden upward shock on inflation can severely hurt economic growth and an inflation cut can be responsible for a take-off. These effects are illustrated quantitatively.